Aplicação do método de indução matemática no ensino médio - Silva, Ednardo Lino da (2015)
This dissertation deals with the importance of using Mathematical Induction Method demonstrations in Basic Mathematics Teaching, because, currently, it is clear that this proof technique is rarely approached at that level of education. For this, we pursue a path that goes from the importance of the demonstrations, followed by a section in which we show the difference between induction and mathematical induction, including the definition and explanation of this method. We also show the equivalence between different forms of the Induction Principle and the Well Ordering Principle. We conclude with the resolution of some examples, followed by suggestions of some problems to facilitate the understanding and application of mathematics Induction Method in High School.